Вплив візуальних новел як жанру на сучасну культуру - Козирєва, А. В. (ХНУРЕ, 2025)
Visual novels, as a distinct genre of interactive art, play an important role in modern culture, influencing literature, the video game industry, cinema, and even education. They combine text, graphics, and music to create a unique narrative experience that allows the player to actively influence the development of the story. This paper examines how visual novels expand the boundaries of traditional narrative, contribute to the development of interactive art forms, and change approaches to storytelling. In addition, their sociocultural impact is analyzed, in particular, on the formation of identity, moral choices, and users' inter action with modern digital media.
Keywords: Visual novels; культура